To Identify Hypertensive Attack and Alert Healthcare Framework using IOT-FOG - Bhanu Prakash Goud Alladi, Sowjanya Masna (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This paper presents a wearable health sensor network system for Internet of Things (IoT) connected safety and health applications. Safety and health of icu patient are important in hospital workplace; therefore, an IoT network system which can monitor all health parameters and update through wireless. The proposed network system incorporates multiple wearable sensors to monitor environmental and physiological parameters. The wearable sensors on different subjects can communicate with each other and transmit the data to a gateway via IoT platform medical signal sensing network. In the proposed system having heart rate, temperature, vibration sensors all integrated to the parallel processing microprocessor. Health parameters re measured by sensors and give the RPI PICO module. This module analyses the data aand monitor in LCD, post the same in internet of things-based server. We continuously monitor, if any changes found like low heart rate, high heart rate, high temperature, patient movement iot alerts the authorized person regarding health A smart IoT gateway is implemented to provide data processing, local web server and cloud connection. After the gateway receives the data from wearable sensors, it will forward the data to an IoT cloud for further data storage, processing, and visualization